(untitled) (Res Medica, 2014)
It is with some reluctance that I start another article, for another magazine, about my elective in India just over a year ago. Not that I feel any ingratitude to the R.M.S. who partly financed my trip but merely because I seem to have been talking about India, its culture, its medicine, its people and problems, from the day I set foot again on the chalky soil of Kent and I ’m beginning to feel a bit of a fraud, rather like the American who spends two weeks in Europe and then starts to profess intimate knowledge of its every nuance the moment he returns home. At the end of two months in India I had seen enough to realise that I’d seen nothing yet. Many impressions remain, of course, and I’d like to focus on just two of them. One of the happiest is that of the wonderful hospitality that we received. The Indian people were, on the whole, astonishingly friendly and helpful despite the linguistic difficulties. The latter were not as great as might be imagined as English is widely spoken among educated Indians, partly because it’s a useful international language, partly as a hang-over of ‘our Indian Empire’. Certainly at the New Civil Hospital in Ahmedabad, a post-war concrete structure with all the architectural grace of the S.M.M.P., the medical students were taught all their medicine in English (despite their previous education in the Gujerati medium), and much of the professional practice was carried on in that tongue. Whilst less than satisfactory for the budding Gujerati anatomist, it was ideal for use as it opened all the necessary professional and social laws.